On Marxist Ethics. Issue 2 (14th March 2016) - Noonan, Jeff
Abstract : A new collection of essays edited by Michael J. Thompson aims to explicate and defend the humanist values which, according to the authors, were the core of Marx's critique of capitalist society. The text does not aim to provide a political roadmap to building an alternative society in which those values could be realized but rather philosophical analysis of the meaning and implications of those values. While there are sometimes tensions between the philosophical arguments developed in the various essays that make up the text and the traditions of Marxist political practice, the book as a whole certainly proves that the human values of Marx's philosophy are central to his politics and that his emancipatory vision remains relevant, even necessary.